Implementation of Pancasila Student Profile-Based Curriculum Management to Improve Student Character at Nurul Ilmi Junior High School, Banyuasin Regency - Yuliani, Husna; Ahyani, Nur; Eddy, Syaiful (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to obtain an overview of the implementation of curriculum management based on Pancasila student profiles to improve the character of students at Nurul Ilmi Junior High School, Banyuasin Regency, starting from the planning, organization, implementation and evaluation stages. The method used in this study is descriptive with a qualitative approach. The data collection techniques used in this study were observation, interviews and documentation. Then the collected data will be analyzed using a triangulation model. It starts with the stage of collecting data, reducing data, presenting data and drawing conclusions. The results of the study show that the implementation of the curriculum based on Pancasila student profiles to improve the character of students at Nurul Ilmi Junior High School has been integrated starting from the planning, organizing, implementation, and evaluation stages of running systematically. At the planning stage, management in improving character is carried out through conditioning every year in the form of work programs and habituation. At the organizing stage, it begins with the formation of a compact and harmonious working group. At the implementation stage, curriculum management is carried out through the process of observing Pancasila student profile project activities, learning processes, and habituation. At the evaluation stage, it was carried out through an assessment process of the results of the P5 report card and the holding of work and art performances. Integrated curriculum management based on Pancasila student profiles is effective in shaping student character and can be a reference for other schools as well as considerations for policy makers.